2020
DOI: 10.1021/acsnano.9b09991
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Sensitive Nanomicelles Enhancing Systemic Delivery of Therapeutically Active Antibodies Specifically into the Brain

Abstract: Delivering therapeutic antibodies into the brain across the blood–brain barrier at a therapeutic level is a promising while challenging approach in the treatment of neurological disorders. Here, we present a polymeric nanomicelle (PM) system capable of delivering therapeutically effective levels of 3D6 antibody fragments (3D6-Fab) into the brain parenchyma for inhibiting Aβ aggregation. PM assembly was achieved by charge-converting 3D6-Fab through pH-sensitive citraconylation to allow complexation with reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…In addition, competitive cellular binding assay of Gal-NP@Cy5-siRNA in general Glut1 inhibitor phloretin treatments showed a dose-dependent uptake in Glut1 highly expressed cells (fig. S4), which is consistent with previous report ( 18 ), indicating Glut1 as the dominant endocytosis pathway. Next, to quantify the efficiency of siRNA silencing of the target gene, BACE1 mRNA and protein expression were examined in Neuro-2a cell samples treated with Gal-NP@siBACE1.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, competitive cellular binding assay of Gal-NP@Cy5-siRNA in general Glut1 inhibitor phloretin treatments showed a dose-dependent uptake in Glut1 highly expressed cells (fig. S4), which is consistent with previous report ( 18 ), indicating Glut1 as the dominant endocytosis pathway. Next, to quantify the efficiency of siRNA silencing of the target gene, BACE1 mRNA and protein expression were examined in Neuro-2a cell samples treated with Gal-NP@siBACE1.…”
Section: Resultssupporting
confidence: 93%
“…Our triple-interaction stabilized siRNA nanomedicine demonstrates superior stability performance in blood circulation relative to conventional cationic polymer-based nanomedicines that feature only a single electrostatic interaction (16). Furthermore, exploiting Glut1 recycling by initially inducing hypoglycemia, which elevates Glut1 expression on the luminal plasma membrane of the BBB, facilitates markedly enhanced delivery of glucose-modified nanocarriers across the BBB when Glut1 is recycled to the abluminal membrane of the BBB upon glucose replenishment (17)(18)(19). To facilitate the Glut1 recycling approach, we appreciated that Glut1 stereochemistry allows binding of both d-glucose and d-galactose (20)(21)(22)(23).…”
Section: mentioning
confidence: 99%
“…Stimuli‐responsive supramolecular systems hold huge potential for application in the area of biomedical sciences [55–57] . Over the last two decades, several groups have made seminal contributions to this field [58–63] . These supramolecular systems have been constructed using a variety of synthetic and biomolecules such as amphiphilic block‐copolymers, [64–67] amphiphilic dendrimer, [68–72] metal nanoparticles, [73] DNA, [74–76] RNA, [77,78] peptides, [79–82] and carbohydrates [83] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, they observed that TVNs could prevent production of cytokines caused by the exposure of Aβ40 (Agyare et al, 2014). Another application of combining polymeric nanoparticles and antibody fragment is studied by Xie et al (2020). The system of polymeric nanomicelle (PM) was provided to deliver 3D6-Fab.…”
Section: The Combination Of Fab Fragments and Polymeric Nanoparticlesmentioning
confidence: 99%